2009
DOI: 10.4103/0019-5413.50853
|View full text |Cite
|
Sign up to set email alerts
|

Fracture healing in India: Available therapies, indications, and protocols

Abstract: The availability of fracture healing therapies to the general public is limited in India. The infrastructure of the health system in India, involving both public and private sectors, does not provide adequate opportunity for rural and low-income inhabitants to access needed care. Also the lack of funding from the government and the overall lack of physicians place a large strain on the system. This paper will take an in-depth look at the state of the current health care system and how it affects bone stimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…1−3 Bone is a dynamic tissue and possess capacity to regenerate but in certain cases such as bone loss by trauma or tumor removal this process in inadequate and requires reconstructive surgery. 4 Autografts are the gold standard 5,6 for treatment of bone defects, but donor site morbidity, and limitations in supply lead to search for alternatives. 7,8 Numerous synthetic materials have been used as bone graft substitutes, e.g., polymers, ceramics, or their composites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1−3 Bone is a dynamic tissue and possess capacity to regenerate but in certain cases such as bone loss by trauma or tumor removal this process in inadequate and requires reconstructive surgery. 4 Autografts are the gold standard 5,6 for treatment of bone defects, but donor site morbidity, and limitations in supply lead to search for alternatives. 7,8 Numerous synthetic materials have been used as bone graft substitutes, e.g., polymers, ceramics, or their composites.…”
Section: Introductionmentioning
confidence: 99%
“…Bone injuries due to sports, trauma, or occupational injuries and low energy fragility fractures and osteoporosis among the elderly significantly impair the quality of life. Bone is a dynamic tissue and possess capacity to regenerate but in certain cases such as bone loss by trauma or tumor removal this process in inadequate and requires reconstructive surgery . Autografts are the gold standard , for treatment of bone defects, but donor site morbidity, and limitations in supply lead to search for alternatives. , Numerous synthetic materials have been used as bone graft substitutes, e.g., polymers, ceramics, or their composites. A material that is resorbable, safe, and inexpensive acts as reservoir of Ca 2+ ions and provides porous surface for migration and proliferation of osteoprogenitor cells will be desired material as bone graft substitute.…”
Section: Introductionmentioning
confidence: 99%
“…Hence the study was undertaken to assess the effectiveness of health education programme on knowledge regarding management of orthopedic appliances among fracture patients and the results showed that, with regard to socio-demographic variables, majority (37.5%) of them were in the age group of 20-30 years and most (55%) of them were males which was contradicted by the study conducted by Swati Kambli [6]. Related to knowledge score, the mean pre test knowledge score was 10.37 with SD of 4.58 where as the mean post test knowledge score was 17.37 with SD of 3.08, while enhancing the mean knowledge score of 7, indicating that health education programme was effective in improving knowledge score among fracture patients and this was supported by the study conducted by Saccone M, Jain AK [7]. With regard to association of knowledge score with selected socio-demographic variables, it was found that there was no association between knowledge with selected socio demographic variables except age.…”
Section: Discussionmentioning
confidence: 65%
“…In addition, to achieve effective bone tissue regeneration, autologous or allogenic bone graft therapy remains the front line treatment, but it needs an additional donor site and cost. Moreover, its success rate is limited by inherent disadvantages such as infection and donor site morbidity [ 13 , 14 , 15 , 16 ]. Nowadays, injectable hydrogel with good biocompatibility has received great attention in the field of bone regeneration as it can be injected and re-expanded to the desired shape in alignment with the defect and serve as an extracellular matrix (ECM) mimic providing a suitable environment for cell growth.…”
Section: Introductionmentioning
confidence: 99%